Green Paradox and Directed Technical Change: The Effect of Subsidies to Clean R&D - Julien Daubanes; André Grimaud; Luc Rougé (Center for Economic Studies and ifo Institute (CESifo), 2013)
We borrow standard assumptions from the non-renewable-resource-taxation and from the directed-technical-change literatures, to take a full account of the incentives to perform R&D activities in a dirty-resource sector and in a clean-resource-substitute sector. We show that a gradual rise in the subsidies to clean R&D activities causes a less rapid resource extraction, because it enhances the long-run resource productivity. Our result contradicts the green-paradox conjecture that technical improvements in resource substitutes accelerate resource extraction. Sector-specific innovation activities are tantamount to competing economic projects; general equilibrium with several R&D sectors implies no-arbitrage conditions that give rise to not-so-intuitive results.
Keywords: Q32; O32; O41; 330; non-renewable resources; directed technical change; green paradox; environmental policy; R&D subsidies